Membaca Al-Qur’an Lewat Layar: Tafsir Populer dan Pesan Dakwah dalam Film Nussa dan Rarra - Dea Aulia, Mifta; Haitomi, Faisal; Muhammad Arif; Rizkiyadi; Muhammad Iqbal Rahman (Ta’wiluna: Jurnal Ilmu Al-Qur'an, Tafsir dan Pemikiran Islam, 2025)
The advancement of technology has led to a diverse reception of the Qur'an, transcending traditional frameworks and manifesting through social media. This article examines the reception of the Qur'an in the animated film "Nussa and Rarra: Pahala Gratis," specifically in the episode titled "Pahala Gratis." The study employs a qualitative research method with a literature review as the data collection technique. The analysis utilizes the reception of the Qur'an in three aspects: exegesis, aesthetics, and functionality, aiming to reveal the impact and interaction between the Qur'anic religious message and the audience. Exegetical reception is evident through the quoting of Qur'anic verses by the character Nussa, specifically QS. al-Aʿrāf[7]: 199, which is then applied within the context of the story. Aesthetic reception is reflected in visual elements, animation, and the use of language, creating an aesthetic experience for the audience. Meanwhile, functional reception involves the implementation of religious values in the daily lives of the audience. The research findings indicate that the animated film "Nussa and Rarra: Pahala Gratis" serves not only as entertainment but also as an effective and creative tool for da'wah (religious outreach). The use of animation technology and creative narrative opens the door for the reception of the Qur'an among a broader audience, proving that religious messages can be conveyed through various forms of media, even those intended for entertainment.